How to Prevent Fraud in Village Financial Management in Kapanewon Tempel? - Nusron, Lulu Amalia (UNIB Press, 2023)
This purpose of the research is to determine the effect of human resource competence, morality, internal control systems, and whistleblowing on the prevention of fraud in village financial management. The type of data in this research is quantitative. This research was conducted in 7 (seven) Kelurahan in Kapanewon Tempel using a questionnaire. The population in this study is the village apparatus as the holder of the power to implement village financial management in Kapanwon Tempel. The sample in this study was 94 respondents consisting of Lurah, Carik, Danarta, Village Consultative Body, and Hamlet in 7 (seven) Kelurahan in Kapanewon Tempel. The sample selection used a non-probability sampling and the data analysis assisted by the SPSS 20 program. The data analysis method used was the multiple linier regression method. The result of the research prove that human resources competence and whistleblowing have no effect on preventing fraud in village financial management, while morality and internal control systems have a positive effect on prevention fraud in village financial management at the Village Government in Kapanewon Tempel. Keywords: Human Resource Competence; Morality; Internal Control System; Whistleblowing; and Final Prevention In Village Financial Management.